MEANS OF LINGUISTIC EXPRESSION AND CINEMATOGRAPHIC VOCABULARY AS MARKER OF INTERMEDIALITY IN M. SPARK'S NOVEL "IN PUBLIC" - Terekhovska, Olena; Lenko, Yuliya (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The article explores the artistic manifestation of intermedial content in Muriel Spark’s novel The Public Image. It is found, in particular, that a significant means of realizing intermediality in the novel is the use of linguistic expressiveness – specifically satire, irony, epithets, metaphors, and comparisons. It is demonstrated that satire and irony are employed to ridicule established social norms and priorities, which the author views as false or even absurd. Epithets, metaphors, and comparisons, in turn, contribute to the creation of vivid artistic imagery. The study also shows that an important tool for the artistic actualization of intermediality in the novel is the use of cinematographic vocabulary and terminology. These elements help achieve a visual effect by participating in the construction of frame-like scenes. It is established that both means of linguistic expressiveness and cinematic vocabulary – functioning as markers of intermediality – play an active role in shaping the novel’s artistic space. These elements enhance the emotional depth of the text, evoking a broader range of feelings and impressions in the reader. Furthermore, they aid in the creation of compelling and memorable images, as well as in portraying original and unpredictable plot developments. This, in turn, captures the reader’s attention and adds to the aesthetic appeal of the text.